Methodological updates for studying the new world of work: revisiting the scale of indicators of pleasure and suffering at work (Research, Society and Development, 2020)
This article aims to present a revisiting of the Scale of Indicators of Pleasure and Suffering at Work (EIPST) published by Mendes (2007) within the scope of the Theory of Psychodynamics of Work, in view of the changes that have occurred in recent years in the world of work , in particular, with the advent of Law 13,467 / 2017, which regulated various forms of non-traditional work. The aim is to update the EIPST; therefore, the following methodological procedures were adopted: visit to the literature on the changes that occurred in the workplace in contemporary times and the relevant literature on the dimensions of pleasure and suffering at work; pre-test; application of the instrument adjusted through Google Forms (171 responses); conducting exploratory factor analysis in SPSS Statistics; and confirmatory factor analysis in SPSS Amos. The results indicated the adequacy of the models and new constructs proposed for the scale: Assistance at Work and Professional Helplessness. However, adjustments were made to the models, either by deleting items or by covariance of errors. The updating of the scale brings a relevant contribution to the field of social and work psychology, as well as to the management that proposes to promote health and well-being of workers, in new work contexts. With the use of it, it will be possible to assess risks of illness at work, arising from contexts with a high degree of suffering from workers, as well as, on the other hand, identifying which dimensions are likely to promote health by enhancing pleasure at work.